2018
DOI: 10.5530/jcdr.2018.3.34
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Abnormalities in Harlequin Ichthyosis: First Case Study

Abstract: Harlequin ichthyosis is the most severe form of congenital ichthyosis and inherited in an autosomal recessive manner. The disease is marked by severe thickened and scaly skin on the entire body. It is a lethal disease, but patients can very rarely survive for several months or years. We present here cardiac abnormalities in a full term baby with Harlequin ichthyosis. To our knowledge, this is first case study to report associated cardiac abnormality in such patients. Further case studies are required to ascert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
(10 reference statements)
0
1
0
Order By: Relevance
“…Previously also, we have reported a case of HI with the presence of OsASD. [12] Though OsASD appears to be a common cardiac abnormality in such babies, the exact incidence is not known. Although our study revealed a high prevalence of congenital heart disease in HI, there clinical significance is not known as the patients either died or refused treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Previously also, we have reported a case of HI with the presence of OsASD. [12] Though OsASD appears to be a common cardiac abnormality in such babies, the exact incidence is not known. Although our study revealed a high prevalence of congenital heart disease in HI, there clinical significance is not known as the patients either died or refused treatment.…”
Section: Discussionmentioning
confidence: 99%